Repair of rotator cuff tears in patients aged 75 years and older: Does it make sense? A systematic review - Meng, Chenyang; Jiang, Boyong; Liu, Ming; Kang, Fujia; Kong, Lingyue; Zhang, Ting; Wang, Caixia; Wang, Jingjuan; Han, Changxu; Ren, Yizhong (Frontiers in Public Health, 2023)
Abstract Background: Rotator cuff injuries are common, and morbidity increases with age. The asymptomatic full-thickness tear rate is 40% in the over 75-year-old population. Purpose: This study aimed to systematically review the literature on the outcomes of rotator cuff repair among >75 years old patients. Study Design: Systematic review. Methods: A systematic review of the literature was performed following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and AMSTAR guidelines (assessing the methodological quality of systematic reviews). A literature search was performed in the electronic databases of PubMed, Medline, Embase, and The Cochrane Library. Studies in English evaluating repair of full-thickness rotator cuff tears in patients aged >75 years were included. Results: Six studies were reviewed, including 311 patients (313 shoulders) treated with arthroscopic and/or open rotator cuff repair. Sixty-one patients were lost to follow-up, leaving 252 shoulders with outcome data. Patients in this age group demonstrated a significant improvement in the clinical and functional scores after rotator cuff repair, with a high satisfaction rate. The mean American Shoulder and Elbow Surgeons scores improved from 43.8 (range, 42.0–45.5) preoperatively to 85.3 (range, 84.0–86.5) postoperatively, and the mean Constant scores improved from 45.4 (range, 34.7–55.5) to 78.6 (range, 67.0–91.6). Pain, evaluated in all studies by the visual analog scale for pain, showed a significant improvement at the last follow-up compared with the mean preoperative score. Furthermore, range of motion and return to daily activities and sports gained marked improvements. Conclusion: Rotator cuff repair in patients aged >75 years could achieve high clinical success rates with good outcomes and pain relief. Although patients in this age group are at a high risk of retear, rotator cuff repair offers a good option with significant functional and clinical improvement.